Optimisme dan resiliensi pada buruh yang terkena dampak pemutusan hubungan kerja (PHK) dimasa pandemi Covid-19 - Ahmad Dian P. Yoga; Diah Sofiah; Yanto Prasetyo (INNER: Journal of Psychological Research, 2022)
Abstract This study aims to determine the relationship between Optimism and Resilience in workers affected by layoffs during the Covid-19 pandemic, this research is included in correlational research. The sample of this study was 60 workers who were affected by layoffs in Krian Sidoarjo. The sampling technique used is Simple Random Sampling. Data collection using Optimism and Resilience scale. The data analysis process uses Spearman-Brown which shows a significant positive relationship between Optimism and Resilience in workers affected by layoffs. The higher the optimism of workers affected by layoffs, the higher the resilience, and vice versa, the lower the optimism, the lower the resilience of workers affected by layoffs during the Covid-19 pandemic. This shows that the hypothesis proposed by the researcher is accepted Keywords: Labor, Optimism, Resilience